The Effect of Parenting Practices on the Severity of Gingival Bleeding in Children. Issue 8 (1st August 2017) - Kumar, Santhosh; Tadakamadla, Jyothi; Zimmer‐Gembeck, Melanie; Kroon, Jeroen; Lalloo, Ratilal; Johnson, Newell W.
Abstract : Background: Studies have consistently reported that parenting practices have an impact on eating styles which determine obesity levels in children. However, to the best knowledge of the authors, there is no study that evaluates the association of parenting practices on gingivitis in children using path analysis to evaluate if oral health–related behavior mediates this association. This study aims to test a model of parenting and family demographic factors that could account for gingivitis in children, with a focus on the mediational roles of oral health–related behaviors and oral hygiene status. Methods: Clinical examination of oral hygiene status and gingivitis was conducted using simplified oral hygiene and modified Community Periodontal Indices, respectively, on sixth‐grade school children (n = 1, 539) of Medak District in Telangana State, India. Children also answered a questionnaire consisting of five closed‐ended questions on oral health–related behavior. Parents responded to queries related to socioeconomic status (SES), family structure, number of children, oral health–related behavior, and parenting practices. Results: Prevalence of gingival bleeding was 92.4%. Power assertion parenting (representing coercive or controlling parenting practices) had a negative effect on oral hygiene status (β = 0.044; P = 0.07), and also had an indirect effect on gingival bleeding (β = 0.011; P = 0.05). Oral hygiene status was positively associated with the extent of gingival bleeding (β = 0.24; P = 0.01). Children living in families with lower SES had worse oral hygiene (β = −0.101; P = 0.01) and gingival bleeding status (β = −0.024; P = 0.01). Conclusion: Power assertion parenting had a deleterious effect on the extent of gingival bleeding via a worse oral hygiene status of children, but SES was also important for predicting oral hygiene and gingival bleeding.